Anti-fungal effect of chloroform crude extract from the leaves of thottea corymbosa / Siti Zaiton Mat So 'ad, Neni Kartini Che Mohd Ramli and Aiza Harun - Mat So'ad, Siti Zaiton; Che Mohd Ramli, Neni Kartini; Harun, Aiza (Universiti Teknologi MARA Cawangan Pahang, 2006)
Bioactivities of the crude extracts from the leaves of Thottea corymbosa were tested on Brine Shrimp Lethality and anti-fungal activity. Three genus of fungal were tested for anti-fungul activity i.e. Rhizoctonia solani, Sclerotium rofsii and Pythium sp., the pathogens of vegetables. The repeated test was done by using other fungi i.e. Aspergillus niger, Aspergillus flavus and Penicillium sp. from the building molds. The in-vitro anti-fungal activities of Thottea corymbosa extracts against microorganism revealed that there was no inhibition zone occured for the three genus of fungal tested. This revealed that there were no anti-fungal activities of crude extract against plant pathogens. The repeated test against the building molds revealed that only chloroform extract had a little anti-fungal activities against Penicillium sp.